2015
DOI: 10.1002/bip.22670
|View full text |Cite
|
Sign up to set email alerts
|

(R)‐α‐trifluoromethylalanine containing short peptide in the inhibition of amyloid peptide fibrillation

Abstract: The extracellular deposition of insoluble amyloid fibrils resulting from the aggregation of the amyloid-β (Aβ) is a pathological feature of neuronal loss in Alzheimer's disease (AD). Numerous small molecules have been reported to interfere with the process of Aβ aggregation. Compounds containing aromatic structures, hydrophobic amino acids and/or the α-aminoisobutyric acid (Aib) as β-sheet breaker elements have been reported to be effective inhibitors of Aβ aggregation. We synthesized two peptides, one contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…The kinetic curve possesses a lag-phase of 5 h, after which fluorescence started to increase in an exponential manner and achieved the stationary phase at 24 h. Our results showed that P4 decreased the final fluorescence intensity by a factor of ≈5.6 and increased the time to attain the plateau. This indicates that P4 executed its anti-amyloidgenic effect by altering the rate of fibril formation of insulin (Botz et al, 2015 ). In contrary, P5 decreased the final fluorescence intensity by a factor of ≈2.5 (almost half as compared with P4) and had insignificant effect on the time to attain the plateau phase.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetic curve possesses a lag-phase of 5 h, after which fluorescence started to increase in an exponential manner and achieved the stationary phase at 24 h. Our results showed that P4 decreased the final fluorescence intensity by a factor of ≈5.6 and increased the time to attain the plateau. This indicates that P4 executed its anti-amyloidgenic effect by altering the rate of fibril formation of insulin (Botz et al, 2015 ). In contrary, P5 decreased the final fluorescence intensity by a factor of ≈2.5 (almost half as compared with P4) and had insignificant effect on the time to attain the plateau phase.…”
Section: Resultsmentioning
confidence: 99%
“…We recently compared the potency of a short ( R )‐ or ( S )‐ α‐trifluoromethylalanine‐containing peptide and its nontrifluoromethylated counterpart for the inhibition of amyloid peptide fibrillation. We hypothesized that the better affinity of the trifluoromethylated peptide for Aβ‐amyloid was the result of enhanced hydrophobic interactions . Looking for experimental evidence, we realized that experimentally derived quantitative data about hydrophobicity measurements of fluorinated amino acids or peptides are scarce and that most hydrophobicity assessments originate from computational fragment methods developed by Leo .…”
Section: Methodsmentioning
confidence: 99%
“…The thioflavin T (ThT) binding assay showed that two of the fluorinated peptides (LVFfFD-PEG and LVfFFD-PEG) are able to delay the aggregation of the Aβ 42 by 1.5 h and 3.1 h. The authors proposed that the position of the fluorine at the extremity of the conjugate seems to influence the hydrophobicity of the sequence. Botz et al [57] synthesized two peptides, one containing the trifluoromethylated (Tfm) analogue (R)-α-trifluoromethylalanine ( Figure 2C) and the other incorporating the nonfluorinated analogue α-aminoisobutyric (Aib). The in vitro studies of these two peptides were evaluated and compared using fluorescence spectroscopy (thought the ThT assay), circular dichroism (CD), and liquid state nuclear magnetic resonance (NMR) for the inhibition of Aβ aggregation.…”
Section: The Role Of Fluorine-containing Compounds In the Modulation mentioning
confidence: 99%